Jenis Lalat Buah Bactrocera spp. (Diptera : Tephritidae) yang Menyerang Pertanaman Jeruk di Kabupaten Gianyar dan Bangli - WIRATAMA, MADE DWIKA; SUSILA, I WAYAN; SUPARTHA, I WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2017)
The Fruit Flies Species (Bactrocera spp.) attacking Citrus Orchard in Gianyar and Bangli Regency of Bali Field research on species composition and attacks of fruit flies was done on citrus orchard located in Gianyar and Bangli Regency of Bali from May up to August 2016. The research aimed to identify and analyze of species composition and attacks of fruit flies attacking the fruit in the field. The research using survey method by collecting of attacked-fruits, purposively on citrus orchard in the field. Adults of fruit flies were identified by identification key of Drew and Hancock (1994). The results indicated that there were two species found on the citrus orchard namely Bactrocera carambolae and Bactrocera papayae The composition of both species were 61 % for B. carambolae and 39 % for B. papayae. B. carambolae was dominant at an altitude of 850 meters above sea level (61.29 % ; 19 adults), 1100 meters above sea level (62.22 % ; 84 adults) and 1200 meters above sea level (68.67%; 57 adults), while B. papayae was dominant at an altitude of 750 meters above sea level (59.32 % ; 35 adults). B. carambolae was also dominant on the variety of Siam, Keprok Selayar and Keprok Batu 55. The affecting factors on the population abundance of fruit fly were affected by the length of cultivation and the number of citrus plant population in each elevation. The average number of adults emerged from an orange fruit was 3 adults while the highest appearance was 11 adults. The highest percentage of fruit flies attacked was at the five months and two week ages of the fruit as much as 7.18 %.